From Diagnosis to Management: A Rare Case of Disseminated Low-Grade Endometrial Stromal Sarcoma with Extensive Extrauterine Spread - Djatikusumo, Adrian; Prastisia, Yulian; Wasystha, Wina Kanya; Effendi, Iwan Kurnia (Indonesian Socety of Obstetrics and Gynecology, 2025)
Objective: To report a rare case of low-grade endometrial stromal sarcoma; which was found not only in the uterus but also in several extrauterine sites, such as the ovary, omentum, and jejuno-ileum. In this article, we provided the management performed, based on appropriate literatures. Methods: Case report. Case: A 44-year old para 2 complained of abdominal enlargement since 3 months. Patient also complained of pelvic pain. The patient has never received treatment before and has never been diagnosed with endometriosis. Abdominal examination revealed a 20-cm mass in the lower to umbilical region and positive shifting dullness. Bimanual pelvic examination revealed immobile and smooth masses in both sides of adnexa, with pain during palpation. Computerized tomography (CT) scan of the abdomen revealed complex cystic masses suspected for right and left ovaries-origin (±11 & 15 cm respectively) Surgical resection and staging, frozen section, cytology examination, and immunohistochemistry (IHC) test were performed, revealing consistent result of endometrioid stromal sarcoma, low grade. Five-months postoperative follow-up through abdominal CT-scan in the patient revealing no abnormalities. Conclusion: We know that LG-ESS is one of the rare types of endometrial stromal sarcoma. Moreover in this case extrauterine manifestations make it more challenging in clinical management. Risk factors and history of endometriosis are important to explore when meeting ESS cases. Further research needs to be done regarding the exact mechanism and the association between endometriosis or other risk factors and the development of ESS, especially the EESS type to allow intervention. Keywords: uterine sarcoma, endometrial stromal sarcoma, management.